Pengaruh Penambahan Serat Kulit Kopi dan Polivinil Alkohol (PVA) terhadap Karakteristik Biodegradable Foam dari Pati Kulit Singkong - Febrina Sarlinda; Amrul Hasan; Zeni Ulma (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2022)
Polystyrene plastic or styrofoam is very popular to be used as a food packaging container even though Styrofoam has a bad impact on health. In addition, Styrofoam also cannot be biodegraded naturally in the environment so the use of syrofoam is also a problem for the environment. One alternative to styrofoam is biodegradable foam (biofoam) made from starch and cellulose. It is safe for health and can be broken down naturally. Cassava peel is rich in starch (carbohydrates) but has low cellulose content. Meanwhile, coffee peel is rich in cellulose and minimal in carbohydrates. Both types of waste have the potential to become biodegradable foam raw materials. The addition of synthetic polyvinyl alcohol (PVA) polymer is expected to improve the mechanical quality of biodegradable foam. This study aims to obtain the best formulation for the manufacture of biodegradable foam from cassava starch with the addition of coffee peel cellulose and PVA. The quality of biofoam evaluated includes tensile strength, water absorption, and biodegradability. The best biofoam characteristics were obtained at the addition of 15% fiber and 15% PVA, resulted in water absorption of 28.87%, the tensile, strength of 2.70 N / mm2, and biodegradability of 93.66% for 30 days.